Introduction to Gangs in America. - Holmes, Ronald M. (CRC Press, 2011)
Gangs The Structure of Gangs Types of Gangs Racial and Ethnic Gangs Chicano/Hispanic Gangs Asian Gangs Types of Gang Members Gang Members: Perpetrators and Victims Gangs and Homicide Defining and Counting Gang Homicides Characteristics of Gang Homicides Who Is Involved Where Gang Homicides Occur How Gang Homicides Are Committed Drive-By Shootings Homicide and Other Criminal Offenses Gang Homicide and Community Crime Rates Gang Homicide and Other Homicides/Assaults Drug Trafficking Gangs and Police Police Response to Gangs Police Gang Units Gang Unit Officers Community Partners Working with Pol.